EE-drospirenone-levomefolate calcium versus EE-drospirenone + folic acid: folate status during 24 weeks of treatment and over 20 weeks following treatment cessation - Diefenbach K; Trummer D; Ebert F; Lissy M; Koch M; Rohde B; Blode H (Dove Medical Press, 2013)
Konstanze Diefenbach,1 Dietmar Trummer,1 Frank Ebert,1 Michael Lissy,2 Manuela Koch,2 Beate Rohde,1 Hartmut Blode3 1Bayer HealthCare Pharmaceuticals, Berlin, Germany; 2Nuvisan GmbH, Neu-Ulm, Germany; 3Bayer HealthCare Pharmaceuticals Global R&D Center, Beijing, People's Republic of China Background: Adequate folate supplementation in the periconceptional phase is recommended to reduce the risk of neural tube defects. Oral contraceptives may provide a reasonable delivery vehicle for folate supplementation before conception in women of childbearing potential. This study aimed to demonstrate that a fixed-dose combination of an oral contraceptive and levomefolate calcium leads to sustainable improvements in folate status compared with an oral contraceptive + folic acid. Methods: This was a double-blind, randomized, parallel-group study in which 172 healthy women aged 18–40 years received ethinylestradiol (EE)-drospirenone-levomefolate calcium or EE-drospirenone + folic acid for 24 weeks (invasion phase), and EE-drospirenone for an additional 20 weeks (folate elimination phase). The main objective of the invasion phase was to examine the area under the folate concentration time-curve for plasma and red blood cell (RBC) folate, while the main objective of the elimination phase was to determine the duration of time for which RBC folate concentration remained ≥ 906 nmol/L after cessation of EE-drospirenone-levomefolate calcium. Results: Mean concentration-time curves for plasma folate, RBC folate, and homocysteine were comparable between treatment groups during both study phases. During the invasion phase, plasma and RBC folate concentrations increased and approached steady-state after about 8 weeks (plasma) or 24 weeks (RBC). After cessation of treatment with levomefolate calcium, folate concentrations decreased slowly. The median time to RBC folate concentrations falling below 906 nmol/L was 10 weeks (95% confidence interval 8–12 weeks) after cessation of EE-drospirenone-levomefolate calcium treatment. Plasma and RBC folate levels remained above baseline values in 41.3% and 89.3% of women, respectively, at the end of the 20-week elimination phase. Conclusion: Improvements in folate status were comparable between EE-drospirenone-levomefolate calcium and EE-drospirenone + folic acid. Plasma and RBC folate levels remained elevated for several months following cessation of treatment with EE-drospirenone-levomefolate calcium. Keywords: drospirenone, ethinylestradiol, folic acid, levomefolate calcium, neural tube defect, oral contraception